Factors Associated with Preventive Behaviors Against COVID-19 SAR-COV-2 among the Adult Population: a Case Study of Chom Thong District, Bangkok Metropolitan - เรือนคำ ปิยะนันท์; คงศีล สุคนธา; เจียมตน สุขุม; สัตยสมบูรณ์ ยุวนุช; อุทิศ เพ็ญพักตร์ (Journal of Health Science of Thailand, 2022)
This cross-sectional analytical study aimed to evaluate the preventive behaviors of COVID-19 and factors associated with preventive behaviors of COVID-19 among 274 participants aged 20-59 years, living in Chom Thong district, Bangkok Metropolitan. PRECEDE-PROCEED model was applied to develop the conceptual framework and multistage sampling technique was employed. The data were collected using self-administered questionnaires and analyzed using descriptive statistics and Chi-squared test. The results showed that 88.45% of participants exhibited preventive behaviors of COVID-19 at good level (mean=12.8, S.D.=2.9). About half of participants reported that they did not cover their mouse or nose when coughing or sneezing and 23.7% reported possible exposure to contaminated fluid by touching their face and mouth, rubbing their eyes and picking their nose. The five factors found significantly associated with preventive behaviors of COVID-19 infections among adults in Chom Thong district (p<0.05) which were sex, marital status, knowledge of COVID-19, enabling factors, and reinforcing factors. The results could be applied in strategic planning and resource allocation to promote access to resources, health services, information about COVID-19 prevention, and engagement of community leaders in COVID-19 prevention efforts, which enabling long-lasting preventive behaviors among community members within the New Normal framework.